2018
DOI: 10.1021/acs.inorgchem.8b01606
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Proton Conductivity of a 3D Metal–Organic Framework by Attaching Guest NH3 Molecules

Abstract: By reaction of a newly designed organic ligand, [3-(naphthalene-1-carbonyl)-thioureido] acetic acid (CHC(O)NHC(S)NHCHCOOH; HL), with Cu(OAc), a metal-organic framework [(CuCuL)·3HO] (1) containing unique mixed-valence [CuCuL] subunits has been successfully synthesized and structurally characterized. MOF 1 displays a three-dimensional open framework bearing one-dimensional channels. Consequently, a new derivative MOF [CuCuL] -NH (2) is procured upon exposure of 1 to NH vapors from 28 wt % aqueous NH solution, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…23,24 Third, the introduction of functional groups to adjust the pore microenvironments of MOFs is another effective approach to improve their proton conductivity. 25 Several specific base/acid groups, including imidazole, 26,27 NH 3 , 28 sulfonic, 29,30 phosphonic, 31 and carboxylic groups, 32,33 have been incorporated into MOFs for enhanced proton conductivity, as they can tune the hydrophilicity of the pore surface, confer protons, and form hydrogen bonds as the proton migration pathway. 34 It is also worth noting that although three-dimensional (3D) protonconductive MOFs have been developed, 2D proton-conductive MOFs are rarely reported.…”
Section: Progress and Potentialmentioning
confidence: 99%
“…23,24 Third, the introduction of functional groups to adjust the pore microenvironments of MOFs is another effective approach to improve their proton conductivity. 25 Several specific base/acid groups, including imidazole, 26,27 NH 3 , 28 sulfonic, 29,30 phosphonic, 31 and carboxylic groups, 32,33 have been incorporated into MOFs for enhanced proton conductivity, as they can tune the hydrophilicity of the pore surface, confer protons, and form hydrogen bonds as the proton migration pathway. 34 It is also worth noting that although three-dimensional (3D) protonconductive MOFs have been developed, 2D proton-conductive MOFs are rarely reported.…”
Section: Progress and Potentialmentioning
confidence: 99%
“…In a different approach that attached the NH 3 molecules onto the framework, Li and co‐workers showed an improvement of proton conductivity by alternating the composition of the ambient gases (NH 3 and water vapor) . The proton conduction value reached 1.13×10 −2 S cm −1 with the influence of ammonia molecules instead of water, with which the proton conduction value was 4.90×10 −4 S cm −1 under 100 °C and 98 % RH conditions.…”
Section: Intoductionmentioning
confidence: 99%
“…It should be pointed out that we recently found that the structure of the 3D MOF [(Cu I 4 Cu II 4 (NCT) 4 )⋅3H 2 O] n (H 3 NCT=[3‐(naphthalene‐1‐carbonyl)‐thioureido] acetic acid) transformed after 2.5 hours of exposure to concentrated NH 3 ⋅H 2 O vapor (14.8 M). In contrast, the two complexes 1 and 2 prepared here maintained their structural stability under low concentration of NH 3 ⋅H 2 O vapor (0.005‐2.0 M).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the related investigation on acyl thiourea carboxylate‐based complexes is relatively limited. Solely our laboratory lately reported the proton conductive properties of an acyl thiourea carboxylate‐based MOF [Cu I 4 Cu II 4 (NCTA) 4 ]⋅3H 2 O} n (H 3 NCTA=[3‐(naphthalene‐1‐carbonyl)‐thioureido] acetic acid) and its NH 3 ‐derivative [Cu I 4 Cu II 4 (NCTA) 4 ] n ‐NH 3 . We found that the NH 3 ‐derivative has a high proton conductivity of 1.13 × 10 −2 S cm −1 at 98% RH and 100 °C, which is much larger than that of [Cu I 4 Cu II 4 (NCTA) 4 ]⋅3H 2 O} n .…”
Section: Introductionmentioning
confidence: 96%